Transverses Abdominis-Plane Block for Postoperative Analgesia in Inguinal Hernia Repair under Spinal Anesthesia - Ravi Kumar, Gotam Kumar, Hiranand, Udesh Kumar, Jai Parkash, Muhammad Arslan Zahid (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare outcome of transverses abdominis plane block versus placebo for postoperative analgesia in inguinal hernia repair under general anaesthesia Study design: Randomized controlled trial Place and duration: Department of Anesthesia Jinnah Postgraduate Medical Centre, Karachi from 6th September 2017 to 6th February 2018 Methodology: One hundred patients with inguinal hernia repair under spinal anaesthesia were enrolled. They were divided into two groups; group A (receiving Bupivacaine) and group B (receiving normal saline). Outcome was checked by comparing both the groups for pain score and analgesic consumption. Results: There were 64(64%) males where as 36(36%) females with mean age of 40.32±6.710 years. In group A, the mean pain score was 4.64±1.54and mean analgesic consumption was 139.38±46.98 while in group B it was 5.62±1.29and 238.30±44.49. Conclusion: The ultrasound directed transversus-abdominis plane block delivers an efficient and virtuous post-operative analgesia method. It also decreases the requirement of analgesic with provision of reliable visual analogue scale scores having reduced complications after the surgery of inguinal hernia. Keywords: Pain score, Analgesic consumption, Spinal anesthesia, Inguinal hernia